COURSE MORPHOLOGICAL CHANGES IN THE SPLEEN MATURE RATS UNDER ADAPTIVE-READAPTATSIYNYH CHANGES IN SKELETAL SYSTEM AND CELLULAR DEHYDRATION ORGANISMS - Гринцова, Н.Б. (World of Medicine and Biology, 2014)
In this paper, morphological analysis of the state of the spleen in terms of reparative regeneration of the tibia in experimental cell dehydration. Revealed various quantitative ratios of the structural components of the white pulp that allows us to consider these changes from the perspective of the processes of adaptation of the organism to pathological factors (dehydration and traumatic agent). Histological study found increased tolerance components to the influence of the spleen cell dehydration in terms of adaptation. The connection expiration, dewatering factor and traumatic agent with deep structural rearrangements body. In the early stages of adaptation mild dehydration does not cause significant changes in the parenchyma and vasculature of the spleen. Increase in terms of adaptation causes reactive changes of the structural components of the spleen.